Biotechnology of probiotic microorganisms' microencapsulation - Starovoitova, Svitlana; Spivak, Mykola (My University, 2022)
The microbiome plays an important role in various physiological processes, including digestion, metabolism, immune responses, biosynthesis of many compounds, elimination of toxins, regulation of gut-brain axis function, and even disease pathogenesis. Most of these microbial communities in the gut are influenced by the mode of birth, feeding of the child, genetic background, and lifestyle, including diet, exercises, stress, medications, and the general health of the host. Intestinal microbial populations can vary significantly from person to person, including healthy individuals. Unfavorable changes in the microbial composition, and hence in its functions, are a characteristic of dysbiosis. In COVID-19, the gut microbiome has been shown to be disrupted after SARS-CoV-2 infection. Existence of a gut-lung axis in which the gut microbiota is metabolically capable of influencing lung function is evidenced.// Мікробіом відіграє важливу роль у різних фізіологічних процесах, включаючи травлення, метаболізм, імунні відповіді, біосинтез багатьох сполук, виведення токсинів, регуляцію функції кишково-мозкової осі та навіть патогенез захворювання. На більшість цих мікробних угрупувань у кишечнику впливають спосіб народження, годування дитини, генетичне походження та спосіб життя, включаючи дієту, фізичні вправи, стрес, ліки та загальний стан здоров’я хазяїна. Популяції кишкових мікробів можуть істотно відрізнятися від людини до людини, включаючи здорових людей. Для дисбактеріозу характерні несприятливі зміни мікробного складу, а отже, і його функцій. Було показано, що при COVID-19 мікробіом кишечника порушується після інфікування SARS-CoV-2. Доведено існування осі кишка-легені, в якій кишкова мікробіота метаболічно здатна впливати на функцію легенів.
Keywords: probiotic microorganisms; microencapsulation; пробіотичні мікроорганізми; мікрокапсулювання; кафедра біотехнології і мікробіології